Synthesis and structures of Boron‐ and Aluminum‐containing spirocycles with P‐P units - Köstler, Wolfgang; Linti, Gerald W. (European journal of inorganic chemistry, 2001)
The reaction of aluminum trichloride with (tBuP)2K2 affords the potassium salt of the candy‐like tricylic compound [(tBuP)8Al2]2−3.With boron trifluoride−dimethyl etherate the bicyclic spiropentane derivative...